Tajikistan Country Gender Assessment - World Bank (Washington, DC, 2015)
The aim of this report is to provide a broad overview of the current state of gender equality in Tajikistan. While the Europe and Central Asia (ECA) region traditionally surpassed many other regions in terms of gender equality, this advantage has been eroding in recent decades. Particularly in Tajikistan, concerns have been raised that men and women have unequally born the consequences of economic, political, and social transitions after independence in 1991. The report examines several dimensions of gender equality both quantitatively and qualitatively. Tajikistan has set up a legal framework that enshrines principles of equality and non-discrimination, but better implementation results require continued efforts. Prevailing social norms and patriarchal systems of decision-making limit women s ability to make effective choices be it at home or at work. The paper is structured along the following lines. The first section introduces the idea of agency that will remain an important issue throughout the report. This is followed by an analysis of disparities in human capital endowment, including health and education. Gender gaps in the Tajik labor market and entrepreneurial activities of men and women are discussed in the fourth and fifth section. The final section concludes with some policy recommendations that might be beneficial for discussions among policy-makers, civil society actors, and development partners.